Piracy and Privateering in the Golden Age Netherlands. - Lunsford, Virginia W. (Palgrave Macmillan, 2007)
This exciting scholarly work examines Dutch maritime violence in the seventeenth-century. With its flourishing maritime trade and lucrative colonial possessions, the young Dutch Republic enjoyed a cultural and economic pre-eminence, becoming the leading commercial power in the world. Dutch seamen plied the world's waters, trading, exploring, and colonizing. Many also took up pillaging, terrorizing their victims on the high seas and on European waterways. Surprisingly, this story of Dutch freebooters and their depredations remains almost entirely untold until now. Piracy and Privateering in the.